2023
DOI: 10.1186/s12864-023-09144-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the REVEILLE family in Rosaceae and role of PbLHY in flowering time regulation

Abstract: Background The circadian clock integrates endogenous and exogenous signals and regulates various physiological processes in plants. REVEILLE (RVE) proteins play critical roles in circadian clock system, especially CCA1 (CIRCADIAN CLOCK ASSOCIATED 1) and LHY (LATE ELONGATED HYPOCOTYL), which also participate in flowering regulation. However, little is known about the evolution and function of the RVE family in Rosaceae species, especially in Pyrus bretschneideri. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…All PbRVE genes in Pyrus bretschneideri leaves under a light/dark cycle exhibited a circadian rhythm. The four PbRVE genes also exhibited robust rhythms under constant light conditions [ 79 ]. In plants, Arabidopsis and Oenanthe javanica grow under various photoperiodic conditions, and the expression of the clock gene Lhcb always decreases from peak levels before dusk and increases from trough levels before dawn.…”
Section: Discussionmentioning
confidence: 99%
“…All PbRVE genes in Pyrus bretschneideri leaves under a light/dark cycle exhibited a circadian rhythm. The four PbRVE genes also exhibited robust rhythms under constant light conditions [ 79 ]. In plants, Arabidopsis and Oenanthe javanica grow under various photoperiodic conditions, and the expression of the clock gene Lhcb always decreases from peak levels before dusk and increases from trough levels before dawn.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we identified four light-responsive proteins ( FKF1 , LHY , RVE1 , and RVE2 ) involved in plant circadian pathways and in the regulation of plant photosynthesis and flowering. Note that few investigations have been conducted on plant anthocyanin synthesis ( Joo et al., 2017 ; Yan et al., 2020 ; Liu et al., 2023 ). The only existing studies showed that after overexpression of RVE8 in Arabidopsis thaliana, the structural genes of the anthocyanin pathway such as 4CL were up-regulated during the day, but this up-regulation was lost at night, suggesting that RVE8 may play a specific role in the influence of light on anthocyanin biosynthesis ( Pérez-García et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also counted the number of differentially expressed MYB genes occured duplications, the results show that 26 gene pairs (59.09%) were identi ed. By annotation of their Arabidopsis homo genes and review of previous studies [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67], the functions of homo genes were brie y annotated. the result show that 13 duplicated genes (30.95%) of homologs are linked to ABA, 11 genes (26.19%) are linked to stress defense, 5 genes (11.90%) are linked to lignin synthesis, and 4 genes (9.52%) are linked to plant optical morphology and circadian rhythms (Table S6).…”
Section: Abiotic Stress Candidate Genesmentioning
confidence: 99%